Dynamic Modelling and Control Studies of a Pilot-Scale Absorption/Stripping System for CO2 Removal for Natural Gas - MARIK SINGH, SALVINDER KAUR (2019)
In the oil and gas industry, the high content of CO2 causes problems to the operation, thus it is essential to remove CO2 from the natural gas. CO2 removal using amine-based solvent in absorption/stripping system is the most widely used technique. Various studies have been done to investigate the dynamic modelling and control strategies for this system. However, most studies reported are mainly focused on post combustion of flue gas at atmospheric condition with low CO2 content. Studies have shown that information obtained at atmospheric pressure could not simply be extrapolated to describe the same phenomena at elevated pressure